2018
DOI: 10.5505/jas.2018.43433
|View full text |Cite
|
Sign up to set email alerts
|

Juliopolis (Iuliopolis) Anthropological Research: Preliminary Results

Abstract: Juliopolis (Iuliopolis) Ankara ili Nallıhan ilçesinde yer alan antik bir kenttir. Juliopolis Nekropolü kazıları 2009 yılından beri Anadolu Medeniyetleri Müzesi Başkanlığınca sürdürülmektedir. Nekropol, Ankara'nın yaklaşık 122 km kuzeybatısında Nallıhan ilçesine bağlı Çayırhan beldesinde bulunmaktadır. Arkeolojik araştırmaya göre nekropol Helenistik Dönem' den itibaren kullanılmaya başlanmış ve Roma Dönemi ve Bizans İmparatorluğu zamanlarında da kullanımı devam etmiştir. Şimdiye kadar 500'ün üzerinde farklı tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…While the ancient city is submerged under Sarıyar Dam Lake, built in the 1950s, the necropolis and remains of an Early Byzantine church dated to 5-6th AD and defense wall are located on the northern shore of the lake (Sağır et al 2015). The salvage excavations, carried out in the necropolis since 2009 by the Museum of Anatolian Civilizations, have uncovered more than 750 tombs of various types (Büyükkarakaya et al 2018). Archaeological nds (e.g., precious and semi-precious jewellery, coins, metal, glass, ceramic and bone artefacts) recovered from these tombs have revealed that the necropolis was used from the Hellenistic period until the Roman and Byzantine Empire periods (Arslan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While the ancient city is submerged under Sarıyar Dam Lake, built in the 1950s, the necropolis and remains of an Early Byzantine church dated to 5-6th AD and defense wall are located on the northern shore of the lake (Sağır et al 2015). The salvage excavations, carried out in the necropolis since 2009 by the Museum of Anatolian Civilizations, have uncovered more than 750 tombs of various types (Büyükkarakaya et al 2018). Archaeological nds (e.g., precious and semi-precious jewellery, coins, metal, glass, ceramic and bone artefacts) recovered from these tombs have revealed that the necropolis was used from the Hellenistic period until the Roman and Byzantine Empire periods (Arslan et al 2012).…”
Section: Introductionmentioning
confidence: 99%